2014
DOI: 10.1093/ije/dyu183
|View full text |Cite
|
Sign up to set email alerts
|

Agent Orange exposure and risk of death in Korean Vietnam veterans: Korean Veterans Health Study

Abstract: Overall, this study suggests that AO/TCDD exposure may account for mortality from various diseases even several decades after exposure. Further research is needed to better understand the long-term effects of AO/TCDD exposure on human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…We identified 187,897 Vietnam War veterans during 1999–2000 with the cooperation of the Ministry of Defense and then the Ministry of Government Administration and Home Affairs ( Yi et al, 2014 ). Among them, 20,000 veterans were selected by a simple random sample.…”
Section: Methodsmentioning
confidence: 99%
“…We identified 187,897 Vietnam War veterans during 1999–2000 with the cooperation of the Ministry of Defense and then the Ministry of Government Administration and Home Affairs ( Yi et al, 2014 ). Among them, 20,000 veterans were selected by a simple random sample.…”
Section: Methodsmentioning
confidence: 99%
“…Since any misclassification of the diagnoses of death could most likely be non-differential according to SBP, potential misclassifications would not be expected to substantially overestimate the hazard ratios. Fourth, our study participants were Vietnam War veterans who have a lower mortality than that expected in the general population [ 18 ], and they had smaller BMIs than those in European-origin populations do. Thus, some of our results may not be generalizable to other populations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of cDNA was performed by the method as described previously . Briefly, the MDCK cells were seeded into 6‐well plates at 1.5 × 10 5 cells/mL concentration and maintained at 37°C with 5% CO 2 for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers and published reports have debated over the usage of 2,4‐D and cancer incidence in humans . In 2014, Sang‐Wook Yi and Heechoul Ohrr concluded that 2,4‐D does not result in cancer incidence on their investigations with several specific cancers …”
Section: Introductionmentioning
confidence: 99%